How important is health inequality for lifetime earnings inequality? - Roozbeh Hosseini; Karen A. Kopecky; Kai Zhao (Federal Reserve Bank of Atlanta, 2021)
Using a dynamic panel approach, we provide empirical evidence that negative health shocks reduce earnings. The effect is primarily driven by the participation margin and is concentrated in less educated individuals and those with poor health. We build a dynamic, general equilibrium, life cycle model that is consistent with these findings. In the model, individuals whose health is risky and heterogeneous choose to either work, or not work and apply for social security disability insurance (SSDI). Health affects individuals' productivity, SSDI access, disutility from work, mortality, and medical expenses. Calibrating the model to the United States, we find that health inequality is an important source of lifetime earnings inequality: nearly 29 percent of the variation in lifetime earnings at age 65 is due to the fact that Americans face risky and heterogeneous life cycle health profiles. A decomposition exercise reveals that the primary reason why individuals in the United States in poor health have low lifetime earnings is because they have a high probability of obtaining SSDI benefits. In other words, the SSDI program is an important contributor to lifetime earnings inequality. Despite this, we show that it is ex ante welfare improving and, if anything, should be expanded.
Keywords: D52; D91; E21; H53; I13; I18; 330; earnings; health; frailty; inequality; disability; dynamic panel estimation; life-cycle models